DISTRIBUSI LOGAM BERAT DALAM AIR DAN SEDIMEN DI PERAIRAN MUARA SUNGAI CISADANE - Rochyatun, Endang; Kaisupy, M Taufik; Rozak, Abdul (UI Scholars Hub, 2006)
Heavy Metallic Element Distribution in Cisadane River Estuary’s Water and Sediment. Observation of heavy metallic elements in Cisadane River Estuary has been done in July and November 2005. The results show that heavy metallic elements content in seawater is lower and still below the treshold value stated by government for fisheries. There was an indication of heavy metallic elements on sediment. Distribution of Pb on July and of Cu on November 2005 were found higher near the coast and decrease towards the sea, and commonly were found in front of estuary such as Cisadane, Muara Saban and Tanjung Pasir. High Pb and Zn distributions on November 2005 were found only in front of Cisadane estuary. Cd distribution of Cisadane estuary was constant at all station but did not show any correlation with the distance of station and estuary. The Cd content on July and November 2005 is lower than 0,001 ppm. Generally, heavy metallic elements content have a uniform distribution at all stations inspite of its distance to estuary